Urgensi Pendidikan Agama Hindu Terhadap Kebijakan Pemerintah Tentang Pendidikan Agama Dan Keagamaan - Ni Wayan Arini; Gusti Nyoman Mastini; Ni Ketut Kantriani (Cetta: Jurnal Ilmu Pendidikan, 2021)
Education is closely related to national development and is directed at the development of all Indonesian people. As an effort to implement the National Education System Law, the government hereby pays great attention to religious education. This study aims to determine the urgency of Hindu religious education on government policies regarding religious and religious education. The method used in this study is a qualitative method using descriptive analysis techniques, with data collection techniques carried out through library research. The results of the study stated that Hindu religious education has a function as a motivator and dynamist, can encourage the creativity of students to do good and right to achieve their life goals, as stated in the Vedas namely Moksartham Jagadhitaya Ca Iti Dharma, meaning that people can practice Hinduism, understand, If you live and practice it, then the purpose of life, namely physical and spiritual well-being, will be achieved in this world and the next life. It is said how great the function of Hinduism is in shaping the character of the nation's children, especially in ethics, morality and morality, developing spirituality in everyday life in order to achieve their life goals. In this context, the government always lists religious education as one of the compulsory subjects that must be taken from elementary school to university. This is reflected in the laws and regulations of the 1945 Constitution and the National Education System Law, as well as other laws and regulations.